DEVELOPING SOFTWARE USING A SYNCHRONOUS APPROACH: KEY PROCESSES AND TOOLS FOR EFFECTIVE DEVOPS - PRAVORSKA, NATALYA; MARTYNYUK, VALERIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This article presents for consideration the method of synchronous execution of the stages of the software life cycle within the framework of DevOps. This method is aimed at increasing productivity in the development and implementation of software products. A thorough study of theoretical issues is carried out, namely aspects of DevOps and synchronous execution of life cycle stages. The implementation of a proprietary method is considered, which is based on the combination of development teams and information and technical service (operators), as well as process automation and continuous quality assurance of the software product. To measure the effectiveness of the simultaneous execution of life cycle stages, the article includes an analysis of metrics, as well as how the proposed method will be influence the speed of solving problems and compliance of the developed projects with the specified requirements and characteristics. The study of the given cases and examples of successful projects in which a synchronous approach was implemented within the framework of DevOps allowed us to draw conclusions about the practical application of this method, as well as its adaptation for projects of various sizes and industries. DevOps is a software development practice that focuses on bringing development and IT teams together to improve productivity, product quality, and cross-team collaboration. Important aspects here are collaboration, automation, integration, deployment, monitoring, feedback, continuous improvement, and elasticity. In DevOps, mutual assistance and sharing of knowledge between teams helps to solve joint tasks. Reducing the number of errors, shortening the time of introducing changes, increasing the efficiency of work processes is possible thanks to the automation of software development processes. Regular code changes and continuous deployment of software in production are ensured by integration and deployment. On the example of successful projects where a synchronous approach within the framework of DevOps was used, a study of the application of the method was conducted and as a result of the study it was found that such an approach can bring significant advantages to organizations. There are special metrics for evaluating the impact of the method on the effectiveness of DevOps processes. The specified metrics were used to measure the efficiency of the synchronous execution of stages. An analysis of the impact of the method on the speed of problem solving and satisfaction with project results was also carried out.